2014
DOI: 10.1002/ar.23089
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor CREB is Involved in CaSR‐mediated Cytoskeleton Gene Expression

Abstract: Our previous studies illustrated that a steady increase of intracellular calcium concentration ([Ca 21 ]i) was important for maintaining microtubules (MTs) rearrangement in apoptotic cells. However, little is known about the effect of calcium sensing receptor (CaSR)-mediated increase in [Ca 21 ]i on cytoskeleton gene expression. We examined the impact of taxol or CaSR agonist/antagonist on the regulation of [Ca 21 ]i concentration, cytoskeleton arrangement, phosphorylated CREB and cytoskeleton gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The constructions of Ser 133 mutant CREB recombination plasmids were finished according to the previous reports [22]. In brief, the CREB coding DNA sequence was amplified by the specific primers [23] and inserted into the EcoR I-Not I site of pCDH-Puro (vector) lentiviral expression vector. The dominant negative plasmid pCDH-CREB-PM-Puro was constructed with Thr instead of Ser 133 by the site-directed mutagenesis kit.…”
Section: Construction Of Lentiviral Vectorsmentioning
confidence: 99%
“…The constructions of Ser 133 mutant CREB recombination plasmids were finished according to the previous reports [22]. In brief, the CREB coding DNA sequence was amplified by the specific primers [23] and inserted into the EcoR I-Not I site of pCDH-Puro (vector) lentiviral expression vector. The dominant negative plasmid pCDH-CREB-PM-Puro was constructed with Thr instead of Ser 133 by the site-directed mutagenesis kit.…”
Section: Construction Of Lentiviral Vectorsmentioning
confidence: 99%
“…In response to various signals, on binding to the cAMP-responsive element (CRE) sequence (TGACGTCA), phosphorylation of CREB (pCREB) at the Ser133 residue is activated by a number of kinases (9). Activated CREB subsequently regulates various cell functions by enhancing the expression of target genes (10)(11)(12). Several studies have demonstrated that overexpression of pCREB promotes tumorigenesis in various cancer tissues, including acute myeloid leukemia (13,14), non-small cell lung carcinoma (15,16), breast (17,18), melanoma (19) and hepatocellular…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the possible role of pCREB in the progression of sorafenib-treated RCC growth and metastasis has not been investigated. In this study, we used the recombinant plasmid pCI-neo/CREB (PN) (constitutively active CREB at Ser-133) (19) to investigate the role of CREB in sorafenib-treated RCC cell lines and demonstrate its effects on cell proliferation and migration under CREB signaling.…”
mentioning
confidence: 99%